2019
DOI: 10.35354/tbed.566076
|View full text |Cite
|
Sign up to set email alerts
|

Alternatif Enerji Kaynakları Teknolojisi ve Enerji Sistemleri Mühendisliği Bölümleri İçin Basit Bir Eğitim Biyogaz Dedektörü Tasarımı

Abstract: Biyogaz metan, karbondioksit, hidrojen sülfit gibi renksiz-kokusuz, yanıcı olan ve organik maddelerin bileşimine bağlı olarak, organik bazlı atıkların anaerobik anaerobik ortamda fermantasyonundan kaynaklanan gazlardan oluşur. Biyogaz teknolojisi ile organik kökenli atıklardan hem enerji elde etmek hem de toprağa atığı geri vermek mümkündür. Aynı zamanda çevre dostu bir enerji ve gübre kaynağıdır. Ev tipi biyogaz tesisleri, kullanım yerlerine yakın yerlerde kullanılmaktadır. Ev tipi biyogaz tesisleri dışındaki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…The CNN model performance was compared with statistical techniques. As a result, it has been observed that the predicted values in the CNN model were compatible with the real average air temperature values (Akyüz et al 2020).…”
Section: Introductıonsupporting
confidence: 61%
“…The CNN model performance was compared with statistical techniques. As a result, it has been observed that the predicted values in the CNN model were compatible with the real average air temperature values (Akyüz et al 2020).…”
Section: Introductıonsupporting
confidence: 61%
“…Akyüz et al [21] the average air temperature of Antalya was estimated by the artificial neural network method. In the study, real monthly average vapor pressure, monthly average relative humidity, related month, and year data were used as an input.…”
Section: Discussionmentioning
confidence: 99%
“…The information coming from the input layer is processed according to certain standards and transmitted to the output layer. The main function of the network is the hidden layer and the number of hidden layers varies from network to network in line with the purpose to be achieved [21]. In this study, since a single hidden layer is sufficient to solve the problem, the best network architecture has been chosen as a single layer architecture with the smallest training, testing and verification errors.…”
Section: Determining the Network Architecturementioning
confidence: 99%